Foundations of twisted endoscopy - Kottwitz Robert E (Paris Societe Mathematique de France, 1999)
This book develops the foundations of a general theory of twisted endoscopy: definition of endoscopic groups, study of the correspondance between twisted conjugacy classes and conjugacy classes in endoscopic groups, definition of transfer factors, and fi
Keywords: Transfer factors; Twisted endoscopy